DBTA-Based Voltage-Mode PID Controller Design - Pratya Mongkolwai; Worapong Tangsrirat (2022 37th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2022)
This paper deals with the design of a voltage-mode proportional-integral-derivative (PID) controller based on the use of differential-input buffered and transconductance amplifiers (DBTAs) as active components. Two DBTAs, four grounded resistors, and two grounded capacitors make up the designed voltage-mode PID controller. A closed-loop control system employing the suggested PID controller was explored to evaluate the performance of the proposed circuit. The proposed PID controller and its utilization in a closed-loop system were simulated with the PSPICE program using the built-in model parameters AD844 and L T1228.
Keywords: Analog and Mixed-Signal Circuit Design; Sensor Technology and Measurement Systems; Advanced Control Systems Design